Maca (Lepidium meyenii) and yacon (Smallanthus sonchifolius) in combination with silymarin as food supplements: in vivo safety assessment - Valentová, Kateřina; Stejskal, David; Bartek, Josef; Dvořáčková, Svatava; Křen, Vladimír; Ulrichová, Jitka; Šimánek, Vilím (Food and chemical toxicology, 2008)
Yacon and maca are native Andean crops with growing popularity as food supplements often in combination with other components, e.g. silymarin. There are however no published data on their toxicity and safety in humans. The aim of our randomized placebo-controlled 90-day study was to evaluate the effects of yacon and maca in combination with silymarin on plasma and lipoprotein lipids, serum glucose and safety parameters in patients suffering from the metabolic syndrome. No adverse effects were found in volunteers using silymarin (0.8 g/day), silymarin+yacon (0.8+2.4 g/day) and silymarin+maca (0.6+0.2 g/day). A moderate AST level and diastolic blood pressure increase was found in volunteers using maca (0.6 g/day). In conclusion, the combination silymarin+yacon appears to be promising as a nutraceutical in the prevention of diseases with a proatherogenic lipoprotein profile and liver steatosis. The effect of maca on AST level and blood pressure must be considered when using high doses of maca powder. This effect could be reversed by supplementation with silymarin.
Keywords: potravní doplňky; silymarin; Adult; Dietary Supplements; Asteraceae; Financing, Organized; lidé středního věku; dospělí; Silymarin; financování organizované; mužské pohlaví; Middle Aged; Lepidium; Humans; lidé; ženské pohlaví; Female; Male